Multiscale lattice Boltzmann modeling of two-phase flow and retention times in micro-patterned fluidic devices. (5th December 2016) - Truszkowska, Agnieszka; Alex Greaney, P.; Jovanovic, Goran
Abstract : Highlights: Multiscale modeling of two-phase flows in microfeatured architectures. Developed with a focus on the dispersed phase retention time. Demonstrated applicability for microarchitecture characterization and optimization. Shown that the posts can be designed to provide size dependent damping force. Abstract: Recent advances for fabricating micro-featured architectures such as posts or pillars in fluidic devices provide exciting opportunities for multiphase flow management. Here we describe a novel, multiscale modeling approach for two-phase flows in microfeatured architectures developed within the Shan and Chen Lattice Boltzmann method. In our approach a fine scale is used to resolve the true microfeatured architecture, with a coarser scale used to model the gross geometry of the device. We develop the basic features of the approach and demonstrate its applicability to modeling retention times of droplets of a dispersed phase in an array of microposts – an architecture used in microfluidic reactors, bioreactors, and biomedical devises. Additionally we show that it is feasible to model the microfeatured geometry in a piecewise manner which includes extrapolating dispersed phase flow characteristics in the entire system based on simulations in smaller subdomains.